The silent war of CMV in aging and HIV infection - Effros, Rita B. (Mechanisms of ageing and development, 2016)
•Importance of to human health.•Replicative senescence within the human immune system.•Senescent T cells accumulate with age.•Cytomegalovirus is a major driver of senescence.•Cytomegalovirus impacts both normal aging and HIV/AIDS. Human cytomegalovirus (CMV), the prototypical β-herpervirus, is a widespread pathogen that establishes a lifelong latent infection in myeloid progenitor, and possibly other cells as well. Although immunocompetent individuals show mild or no symptoms despite periodic reactivation during myeloid cell differentiation, CMV is responsible for considerable morbidity and mortality in older adults and in persons chronically infected with HIV. Indeed, in these individuals, reactivation of CMV can cause serious complications. This review will focus of the effects of CMV during aging and HIV/AIDS, with particular attention to the cellular immunity and age-related pathology outcomes from this persistent infection. The impact of the long-term chronic exposure to CMV antigens on the expansion of CD8 T cells with features of replicative senescence will be highlighted.